Different methods of finishing and polishing enamel - Giampaolo, E. T.; Machado, Ana Lucia [UNESP]; Pavarina, Ana Claudia [UNESP]; Vergani, Carlos Eduardo [UNESP] (Mosby, Inc, 2003)
Statement of problem. Highly polished enamel surfaces arc recommended for axial tooth surfaces that will serve as guiding planes and be contacted by component parts of a removable partial denture. There is little evidence to support the assumption that this tooth modification will provide accurate adaptation of the framework and prevent build-up of plaque.Purpose. The aim of this investigation was to evaluate the surface roughness of the tooth enamel, prepared to serve as guiding planes, with different polishing systems.Material and methods. Four different methods (designated A, B, C, and D) for finishing and polishing the prepared enamel surfaces of 20 freshly extracted third molar teeth were studied. Each method involved 3, 4, or 5 different steps. The roughness of each specimen was measured at the start of each method before recontouring, after recontouring, and after each step of the 4 finishing and polishing procedures. The 4 experimental finishing methods were applied after recontouring the axial surfaces (buccal, lingual, and proxinial) of each tooth. Thus the 20 teeth (60 surfaces) were finished and polished by use of 1 of the experimental methods. Surface roughness was measured with a profilometer (mum); the readings of the unpolished enamel Surfaces were recorded as control measurements. Results were statistically analyzed with one-way analysis of variance followed by Tukey's test at the 95% level of confidence.Results. The highest roughness mean values (14.41 mum to 16.44 mum) were found when the diamond bur was used at a high speed for tooth preparation. A significant decrease in roughness values was observed with the diamond bur at a low speed (P<.05). Analysis of the roughness values revealed that all polishing methods produced surface roughness similar to that of the corresponding control teeth.Conclusion. Within the limitations of this study, all finishing procedures tested effectively promoted an enamel surface similar to the original unpolished enamel.